Retort beef aroma that gives preferable properties to canned beef products and its aroma components. (28th July 2017) - Migita, Koshiro; Iiduka, Takao; Tsukamoto, Kie; Sugiura, Sayuri; Tanaka, Genichiro; Sakamaki, Gousuke; Yamamoto, Yasufumi; Takeshige, Yusuke; Miyazawa, Toshio; Kojima, Ayako; Nakatake, Tomoko; Okitani, Akihiro; et al.
Abstract: The objective of this study is to identify the properties and responsible compounds for the aromatic roast odor (retort beef aroma) that commonly occurs in canned beef products and could contribute to their palatability. The optimal temperature for generating retort beef aroma was 121°C. An untrained panel evaluated both uncured corned beef and canned yamato‐ni beef and found that they had an aroma that was significantly ( P  <   0.01) similar to the odor of 121°C‐heated beef than 100°C‐heated beef. The panel also noted that the aroma of 121°C‐heated beef tended to be ( P  <   0.1) preferable than that of 100°C‐heated beef. These results suggest that retort beef aroma is one constituent of palatability in canned beef. GC‐MS (gas chromatography‐mass spectrometry) analysis of the volatile fraction obtained from 100°C‐ and 121°C‐heated beef showed that the amounts of pyrazine, 2‐methylpyrazine and diacetyl were higher in the 121°C‐heated beef than in the 100°C‐heated beef. GC‐sniffing revealed that the odor quality of pyrazines was similar to that of retort beef aroma. Therefore, pyrazines were suggested to be a candidate responsible for the retort beef aroma. Analysis of commercial uncured corned beef and cured corned beef confirmed the presence of pyrazine, 2‐methylpyrazine and 2, 6‐dimethylpyrazine.